Qualitative phytochemical analysis on psidium guajava leaves extracts and its inhibition effects on human osteosarcoma cells - Ruslan, Nor Farhana (Universiti Sains Malaysia, 2009)
The world of modem medicine is now beginning to accept the use of botanicals once they are scientifically validated. One example is the Psidium guajava or commonly known as guava. The leaves of Psidium Guajava (PG) is very well known for its vast traditional uses and purposes. One of the areas in concern is the potential chemo preventive activities. The objective of this study is to perform qualitative phytochemical evaluation on the extracts of PG leaves (methanol extract, petroleum ether extract and water extract) and also to determine the inhibition concentration (IC50) of the extract on the osteosarcoma cell lines (CRL 1543). Leaves collected from one of the local household in the Kelantan state is processed, and extracted using three different types of solvents, namely petroleum ether (PE), methanol and water. The qualitative phytochemical analysis done on the extracts showed that the methanol and water extracts contain alkaloids, tannins and saponms. The petroleum ether (PE) extract on the other hand contains only alkaloids and terpenoid. The methanolic extract showed significant growth reduction activity in CRL 1543 and the IC50 concentration of the methanolic extract on CRL 1543 is approximately 50 ug/ml (p value< 0.05)